Honeycomb layered oxides: structure, energy storage, transport, topology and relevant insights. (12th February 2021) - Kanyolo, Godwill Mbiti; Masese, Titus; Matsubara, Nami; Chen, Chih-Yao; Rizell, Josef; Huang, Zhen-Dong; Sassa, Yasmine; Månsson, Martin; Senoh, Hiroshi; Matsumoto, Hajime
Abstract : A review to delineate the chemistry and physics for honeycomb layered oxides. Abstract : The advent of nanotechnology has hurtled the discovery and development of nanostructured materials with stellar chemical and physical functionalities in a bid to address issues in energy, environment, telecommunications and healthcare. In this quest, a class of two-dimensional layered materials consisting of alkali or coinage metal atoms sandwiched between slabs exclusively made of transition metal and chalcogen (or pnictogen) atoms arranged in a honeycomb fashion have emerged as materials exhibiting fascinatingly rich crystal chemistry, high-voltage electrochemistry, fast cation diffusion besides playing host to varied exotic electromagnetic and topological phenomena. Currently, with a niche application in energy storage as high-voltage materials, this class of honeycomb layered oxides serves as ideal pedagogical exemplars of the innumerable capabilities of nanomaterials drawing immense interest in multiple fields ranging from materials science, solid-state chemistry, electrochemistry and condensed matter physics. In this review, we delineate the relevant chemistry and physics of honeycomb layered oxides, and discuss their functionalities for tunable electrochemistry, superfast ionic conduction, electromagnetism and topology. Moreover, we elucidate the unexplored albeit vastly promising crystal chemistry space whilst outlining effective ways to identify regions within this compositional space, particularly where interesting electromagnetic and topological properties could be lurking within the aforementioned alkali and coinage-metal honeycomb layered oxide structures. We conclude by pointing towards possible future research directions, particularly the prospective realisation of Kitaev–Heisenberg–Dzyaloshinskii–Moriya interactions with single crystals and Floquet theory in closely-related honeycomb layered oxide materials.